Employee Empowerment and Job Satisfaction: A Literature Review - Ananda Sulistio; Ismi Darmastuti (Arthatama: Journal of Business Management and Accounting, 2022)
This literature review employs a scoping review methodology to synthesize research on the relationship between employee empowerment and job satisfaction across organizational contexts. The research begins by defining the primary question: how does employee empowerment impact job satisfaction in various industries? A review protocol is developed, setting specific inclusion criteria for studies published between 2019 and 2024, with additional supporting studies from 2014 to 2018. Exclusion criteria include studies not in English or Indonesian, or those not directly related to the topic. Relevant studies are gathered from databases such as ProQuest, Emerald, Scopus, and ResearchGate, using keywords like "employee empowerment" and "job satisfaction." The literature is initially screened through titles and abstracts, followed by a full review of the remaining articles. Data extraction is performed using a chart to capture key information including author details, research focus, methodology, and findings related to empowerment and job satisfaction. Finally, the findings are synthesized, offering insights into the various ways employee empowerment enhances job satisfaction across different organizational settings. This approach provides valuable guidance for future research and organizational practices, demonstrating the significant role of empowerment in improving employee job satisfaction.